SISTEM KEAMANAN KOMPUTER - MUHAMMAD FAKHRI; KARINA ASMARA (LP2MTBM MAKARIOZ, 2022)
Computer security which is considered unimportant by many people can actually bring great harm to that person. If examined further, it turns out that there are many things that can threaten a person's personal data through computer media. Currently there are many programs that are malicious such as viruses, worms, trojans and others which when infecting our computer systems can cause harm to us. The research is not only based on personal experience, but also summarized from various library sources obtained from the internet where with internet media we can find out what crimes have occurred caused by the malicious software. The way to secure our computers from malicious software attacks is by using a program called an anti-virus. With this anti-virus program, we can at least prevent malicious software from entering our computers, even though we may not feel comfortable using the anti-virus. As many people say, if you want to be safe it will not be comfortable